2023
DOI: 10.1177/14624745231166311
|View full text |Cite
|
Sign up to set email alerts
|

Prosecutors as punishers: A case study of Trump-era practices

Abstract: Recent punishment and society scholarship has addressed the limits of policy reforms aimed at reducing mass incarceration in the U.S. This work has focused in particular on the political dimensions of penal legal reform and policy-making, and the compromises and shortcomings in those processes. Nearly absent in this scholarship, however, has been empirical and theoretical engagement with the role of front-line prosecutors as facilitators and/or resistors to downsizing efforts. Using the case of the U.S. federa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 48 publications
1
5
0
Order By: Relevance
“…While this is not a unique problem, other research suggests that criminal justice actors in other places have worked to circumvent restrictions on public housing precisely because they know it provides stable addresses for people (Bonnet, 2019). Our results also provide an interesting comparison to Lynch's (2023) findings around prosecutorial resistance to reforms. In this case, court actors largely embraced reforms but were still stymied by the legal structure and organizational practices of the court, especially early on.…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…While this is not a unique problem, other research suggests that criminal justice actors in other places have worked to circumvent restrictions on public housing precisely because they know it provides stable addresses for people (Bonnet, 2019). Our results also provide an interesting comparison to Lynch's (2023) findings around prosecutorial resistance to reforms. In this case, court actors largely embraced reforms but were still stymied by the legal structure and organizational practices of the court, especially early on.…”
Section: Discussionsupporting
confidence: 52%
“…Additionally, pre-existing organizational practices shape interpretation of new policies (Verma, 2015), suggesting that even if new programs are implemented, broad penal practices often remain stable (Beckett et al, 2018). For example, Lynch (2023) found that reform efforts were undermined by federal prosecutors dedicated to maintaining punitive approaches through charging and plea bargaining under the Trump administration. These studies suggest that examining organizations over time is important for understanding how these practices are not only constantly negotiated in a dynamic way, but also might shift as programs develop.…”
Section: Coercive Penal Care and Hybrid Governancementioning
confidence: 99%
See 1 more Smart Citation
“…In most U.S. parole systems (Cassidy, 2019), and some Australian, African (van Zyl Smit and Appleton, 2019), and Asian jurisdictions (Ono, 2023), the State's representatives, such as prosecutors and similar officials, play a role in lifers’ parole process by expressing their opinions during the parole hearings. Although scholars have made considerable efforts in exploring the work of State representatives at sentencing (Barkow, 2021; Wright and Levine, 2018; Lynch, 2023), their parole work has remained largely understudied (a recent exception is Aviram, 2020). This neglect aligns with the common view of prosecutors’ work as ending when the judge's gavel falls and as detached from the implementation of punishment (Barkow, 2021; Lynch, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Although scholars have made considerable efforts in exploring the work of State representatives at sentencing (Barkow, 2021; Wright and Levine, 2018; Lynch, 2023), their parole work has remained largely understudied (a recent exception is Aviram, 2020). This neglect aligns with the common view of prosecutors’ work as ending when the judge's gavel falls and as detached from the implementation of punishment (Barkow, 2021; Lynch, 2023). In addition, the focus of parole literature has been on the professional identity of parole board members rather than on other parole actors (Guiney, 2022; Young and Pearlman, 2022).…”
Section: Introductionmentioning
confidence: 99%